Effect of Pr- and Nd-doping on structural, dielectric, and magnetic properties of multiferroic Bi0.8La0.2Fe 0.9Mn0.1O3 - Singh R.; Dwivedi G.D.; Shahi P.; Kumar D.; Prakash O.; Ghosh A.K.; Chatterjee S. (My University, 2025)
Bi0.8La0.15RE0.05Fe0.9Mn 0.1O3 (where RE = Pr and Nd) have been prepared via conventional solid state route. The Rietveld refinement of X-ray diffraction patterns shows that both systems crystallize in orthorhombic Pnma space group. Raman modes observed for these two systems indicate that both systems are very close to orthorhombic Pnma structure. Appearance of prominent A1-3 and weak E-2 modes in Bi0.8La0.15Nd0.05Fe 0.9Mn0.1O3 indicate the presence of chemically more active Bi-O covalent bonds (which favors stereochemical activity of Bi lone pair electrons) in comparison to Bi0.8La0.15Pr 0.05Fe0.9Mn0.1O3. Moreover, Bi 0.8La0.15Nd0.05Fe0.9Mn 0.1O3 system shows higher dielectric constant, low dielectric loss, and higher magnetization value in comparison to Bi 0.8La0.15Pr0.05Fe0.9Mn 0.1O3 system. Ferroelectric transition temperature decreases to 460 °C for both systems in comparison to 710 °C of Bi 0.8La0.2Fe0.9Mn0.1O3. The improved dielectric and magnetic response suggests Bi0.8La 0.15Nd0.05Fe0.9Mn0.1O3 a better multiferroic system than Bi0.8La0.15Pr 0.05Fe0.9Mn0.1O3. © 2014 AIP Publishing LLC.